Impact of a pharmacist intervention at an intensive care rehabilitation clinic. Issue 3 (27th September 2019) - MacTavish, Pamela; Quasim, Tara; Shaw, Martin; Devine, Helen; Daniel, Malcolm; Kinsella, John; Fenelon, Carl; Kishore, Rakesh; Iwashyna, Theodore J; McPeake, Joanne
Abstract : Objective: While disruptions in medications are common among patients who survive critical illness, there is limited information about specific medication-related problems among survivors of critical care. This study sought to determine the prevalence of specific medication-related problems detected in patients, seen after critical care discharge. Design: Consecutive patients attending an intensive care unit (ICU) follow-up programme were included in this single-centre service evaluation. Setting: Tertiary care regional centre in Scotland (UK). Participants: 47 patients reviewed after critical care discharge at an ICU follow-up programme. Interventions: Pharmacists conducted a full medication review, including: medicines reconciliation, assessing the appropriateness of each prescribed medication, identification of any medication-related problems and checking adherence. Measurements: Medication-related problems in patients following critical care discharge. Interventions and medication-related problems were systematically graded and risk factors were identified using an adapted version of the National Patient Safety Agency Risk Matrix. Main results: 69 medication-related problems were identified in 38 (81%) of the 47 patients. The most common documented problem was drug omission (29%). 64% of the medication-related problems identified were classified as either moderate or major. The number of pain medications prescribed at discharge from intensive care was predictive of medication-related problems (OR 2.02, 95% CI 1.14 to 4.26, p=0.03). Conclusions: Medication problems are common following critical care. Better communication of medication changes both to patients and their ongoing care providers may be beneficial following a critical care admission. In the absence of highly effective communication, a pharmacy intervention may contribute substantially to an intensive care rehabilitation or recovery programme.